Pertanggungjawaban Hukum Bank Sulselbar dalam Pemberian Kredit: Suatu Analisis Yuridis - Anita Sari; Muhammad Sabir; Herman Balla; Bakhtiar Tijjang; Muh. Akbar Fhad Syahril (Jurnal Litigasi Amsir, 2026)
This study aims to analyze the legal provisions governing the granting of credit by Bank Sulselbar and the mechanism for granting credit by Bank Sulselbar. Using a normative research method, the results show that the legal provisions governing credit provision at Bank Sulselbar are based on the 1998 Banking Law and reinforced by the 2023 P2SK Law, which emphasizes the principles of prudence, risk management, and good governance. Technical regulations from the OJK and Bank Indonesia regulate creditworthiness assessment, risk supervision, and money laundering prevention through the KYC principle. Internally, Bank Sulselbar implements the Bank Credit Policy (KPB), Credit Granting SOP, and Guidelines for Handling Non-Performing Loans as a form of implementing prudential principles. The credit granting mechanism is carried out systematically through the stages of administration, interviews, field surveys, agreement signing, and credit realization. The 5C principle is used as the main instrument to assess eligibility and risk, so that credit is channeled to debtors who are truly capable of fulfilling their obligations. This mechanism maintains the quality of the credit portfolio, financial stability, and public trust in Bank Sulselbar.